Testing the Non-Linear Relationship between Liquidity Risk and Bank Stability in the MENA Region - Khemiri, Mohamed Ali (International Journal of Economics and Financial Issues, 2022)
This paper aims to investigate whether the relationship between liquidity risk and bank stability is non-linear. It uses a sample of 83 MENA banks from 2005 to 2020. Due to several economic, financial, and regulation differences, the whole sample was divided into two sub-samples. The first one is related to Middle East countries and covers 56 banks while the second one is related to North African countries and covers 27 banks. We performed the Panel Smooth Threshold Regression (PSTR) model proposed by González et al. (2005) as an empirical approach. The empirical results indicate that exists a threshold effect in the liquidity risk-bank stability relationship. More specifically, we found that below a certain threshold, the loan to-deposit-ratio does not exert any significant effect on bank stability in the Middle East; while it significantly increases the stability of banks in North African countries. Above, the same threshold, the loan-to-deposit ratio significantly decreases bank stability for the two sub-samples.